Antiepileptic geissoschizine methyl ether is an inhibitor of multiple neuronal channels - Xie Zhu-qing; Tian Xiao-ting; Zheng Yue-ming; Zhan Li; Chen Xue-qin; Xin Xiao-ming; Huang Cheng-gang; Gao Zhao-bing (Acta Pharmacologica Sinica, 2020)
Geissoschizine methyl ether (GM) is an indole alkaloid isolated from Uncaria rhynchophyll (UR) that has been used for the treatment of epilepsy in traditional Chinese medicine. An early study in a glutamate-induced mouse seizure model demonstrated that GM was one of the active ingredients of UR. In this study, electrophysiological technique was used to explore the mechanism underlying the antiepileptic activity of GM. We first showed that GM (1−30 μmol/L) dose-dependently suppressed the spontaneous firing and prolonged the action potential duration in cultured mouse and rat hippocampal neurons. Given the pivotal roles of ion channels in regulating neuronal excitability, we then examined the effects of GM on both voltage-gated and ligand-gated channels in rat hippocampal neurons. We found that GM is an inhibitor of multiple neuronal channels: GM potently inhibited the voltage-gated sodium (NaV), calcium (CaV), and delayed rectifier potassium (IK) currents, and the ligand-gated nicotinic acetylcholine (nACh) currents with IC50 values in the range of 1.3−13.3 μmol/L. In contrast, GM had little effect on the voltage-gated transient outward potassium currents (IA) and four types of ligand-gated channels (γ-amino butyric acid (GABA), N-methyl-D-aspartate (NMDA), α-amino-3-hydroxy-5-methylisoxazole-4-propionate/kainite (AMPA/KA receptors)). The in vivo antiepileptic activity of GM was validated in two electricity-induced seizure models. In the maximal electroshock (MES)-induced mouse seizure model, oral administration of GM (50−100 mg/kg) dose-dependently suppressed generalized tonic-clonic seizures. In 6-Hz-induced mouse seizure model, oral administration of GM (100 mg/kg) reduced treatment-resistant seizures. Thus, we conclude that GM is a promising antiepileptic candidate that inhibits multiple neuronal channels.